Aerobic Vaginal Microflora in Gestational and Non-Gestational Bitches (Canis lupus familiaris) - Pop R. A.; Vasiu I.; Meroni G.; Martino P.; Dabrowski R.; Tvarijonaviciute A.; Fit I. N. (Animals, 2024)
The vaginal tract comprises commensal microorganisms, which play an essential role in the health of the reproductive tract. Any dysbiosis in the vaginal microenvironment may lead to severe urinary tract infections or even infertility. This study aimed to evaluate the aerobic bacterial flora isolated from vaginal samples from 100 lactating bitches in the antepartum period (n = 3), postpartum period (n = 80), and with Lactatio sine graviditate (n = 17). Before vaginal swabs, all the bitches went through a gynecology consult, along with milk and blood sampling. Standard microbiological techniques were used for bacterial isolation. Among the 100 vaginal samples analyzed, 82% had a positive microbiological outcome, while 18% were negative. The microbiologic profile listed 17 different genera. The main isolated bacterial families were Micrococcaceae, Staphylococcaceae, Morganellaceae, Bacillaceae, and Rhizobiaceae. At the same time, strains like Agrobacterium radiobacter, Ochrobactrum anthropi, Chromobacterium violaceum, Burkholderia mallei, Bacillus pumllus, or Staphylococcus xylosus were isolated for the first time from the vaginal secretion of lactating bitches. The microbiological data demonstrates that lactating bitches' vaginal discharge is heterogeneous and may be affected by coitus, sampling season, age, and reproductive status.